2009
DOI: 10.1158/1078-0432.ccr-08-1901
|View full text |Cite|
|
Sign up to set email alerts
|

Grape Seed Proanthocyanidins Inhibit the Growth of Human Non-Small Cell Lung Cancer Xenografts by Targeting Insulin-Like Growth Factor Binding Protein-3, Tumor Cell Proliferation, and Angiogenic Factors

Abstract: Purpose: Lung cancer is a leading cause of cancer-related deaths worldwide. Here, we assessed the chemotherapeutic effect of grape seed proanthocyanidins (GSPs) on human non-small cell lung cancer (NSCLC) cells in vitro and in vivo using a tumor xenograft model. Experimental Design: The effects of GSPs on human NSCLC cell lines in terms of cellular proliferation were determined. The chemotherapeutic effects of a GSP-supplemented AIN76A control diet fed to nude mice bearing tumor xenografts (A549 and H1299) wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
80
1
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 89 publications
(88 citation statements)
references
References 32 publications
5
80
1
2
Order By: Relevance
“…Recently, we found that dietary GSPs resulted in the significant inhibition of the growth of human non-small cell lung cancer (NSCLC) cell xenografts in nude mice and that this was associated with the inhibition of lung tumor cell proliferation and the inhibition of angiogenic factors (28). In the present study, we investigated the mechanism responsible for the inhibition of lung cancer cell proliferation using in vitro and in vivo models.…”
Section: Introductionmentioning
confidence: 86%
See 4 more Smart Citations
“…Recently, we found that dietary GSPs resulted in the significant inhibition of the growth of human non-small cell lung cancer (NSCLC) cell xenografts in nude mice and that this was associated with the inhibition of lung tumor cell proliferation and the inhibition of angiogenic factors (28). In the present study, we investigated the mechanism responsible for the inhibition of lung cancer cell proliferation using in vitro and in vivo models.…”
Section: Introductionmentioning
confidence: 86%
“…The effect of GSPs on the proliferative capacity of the cells was determined using the MTT assay as previously described (28). The effect of GSPs on cell viability was assessed as the percent cell viability compared with vehicle-treated control cells, which were arbitrarily assigned 100% viability.…”
Section: Cell Proliferation Assaymentioning
confidence: 99%
See 3 more Smart Citations